Spatial patterns of hypolithic cyanobacterial diversity in Northern Australia. Issue 17 (31st July 2017) - Christian, Keith; Kaestli, Mirjam; Gibb, Karen
Abstract: Photosynthetic microbial communities under translucent rocks (hypolithic) are found in many arid regions. At the global scale, there has been little intercontinental gene flow, and at a local scale, microbial composition is related to fine‐scale features of the rocks and their environment. Few studies have investigated patterns of hypolithic community composition at intermediate distances. We examined hypolithic cyanobacterial diversity in semi‐arid Australia along a 10‐km transect by sampling six rocks from four adjacent 1 m 2 quadrats ("distance zero") and from additional quadrats at 10, 100, 1, 000, and 10, 000 m to test the hypothesis that diversity would increase with the number of rocks sampled and distance. A total of 3, 108 cyanobacterial operational taxonomic units (OTUs) were detected. Most were neither widespread nor abundant. The few that were widespread tended to be abundant. There was no difference in the community composition between the four sites at distance zero, but the samples 10 m away were significantly different, as were those at all other distances compared to distance zero. Many additional OTUs were recorded with increasing distance up to 100 m. These patterns of distribution are consistent with a colonization model involving dispersal from rock to rock. Our results indicate that distance was a significant factor that can be confounded by interrock differences. Most diversity was represented in the first 100 m of the transect, with an additional 1.5% of the total diversity added by the sample at 1 km, but only 0.2% added with the addition of the 10‐km site. Abstract : We examined hypolithic cyanobacterial diversity in semi‐arid Australia along a 10‐km transect by sampling six rocks from four adjacent 1 m 2 quadrats ("distance zero") and from additional quadrats at 10, 100, 1, 000, and 10, 000 m to test the hypothesis that diversity would increase with the number of rocks sampled and distance. There was no difference in the community composition between the four sites at distance zero, but the samples 10 m away were significantly different, as were the communities at all other distances when compared to distance zero. Substantial numbers of additional OTUs were recorded with increasing distance up to 100 m.